2018
DOI: 10.3168/jds.2017-13045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminized reflective hutch covers on calf health and performance

Abstract: The effect of polyethylene hutches wrapped in aluminized reflective covers (ARC) on health and performance of pre-weaned Holstein heifers during summer was evaluated. Ambient and hutch temperature and temperature-humidity index (THI) were also assessed. The study was conducted from June to October 2016 where temperature, humidity, and THI ranged from -1.3 to 38.4°C, 9.8 to 99.7%, and 33.6 to 81.1 units, respectively. Heifers enrolled at 1 d of life and housed in individual polyethylene hutches with (covered) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
11
2
Order By: Relevance
“…Pre-weaning management and housing of calves in this operation were previously described [29, 30]. Briefly, after receiving colostrum, calves were transferred to the rearing facility during the first day of life.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-weaning management and housing of calves in this operation were previously described [29, 30]. Briefly, after receiving colostrum, calves were transferred to the rearing facility during the first day of life.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of hutch material, temperatures above 29 • C inside the hutches have been reported (147). Even in moderate U.S climates, the average hutch interior can reach 22.8 • C and a THI of 68 in summer, indicating severe heat stress (148). A study in Arizona reported the highest THI, highest cortisol levels, lower circulating IgG, and higher incidence of mortality in calves housed in portable-solid wall hutches, compared to improved housing systems by provision of shade and pre-cooled air (149).…”
Section: Management Interventionsmentioning
confidence: 99%
“…A detailed description of the calves’ management at birth and in the rearing facility (housing, feeding, dehorning and vaccination program) was published [25]. In general, calves were immediately separated from their dam at birth, fed 2.8 L of colostrum during the first hour of life and at 3 and 8 h of life.…”
Section: Methodsmentioning
confidence: 99%